The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1055/s-0038-1656337
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Gel Network Characteristics and Coronary Heart Disease: Relations to Plasma Fibrinogen Concentration, Acute Phase Protein, Serum Lipoproteins and Coronary Atherosclerosis

Abstract: SummaryThe native fibrin gel structure formed in vitro from plasma samples was examined by liquid permeation of the hydrated fibrin gel networks in 18 men who had suffered a myocardial infarction before the age of 45 years and in 20 control subjects. Patients with an elevated plasma fibrinogen concentration had a considerably lower fibrin gel porosity (permeability coefficient, K s) compared with patients with a normal plasma fibrinogen level and with controls. The calculated fiber mass-length ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
3
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 38 publications
(47 reference statements)
6
110
3
4
Order By: Relevance
“…In the present study, the most powerful determinants of fibrin gel permeability (Ks) were changes in levels of P-fibrinogen and cholesterol. These findings are in line with studies by Fatah et al [11,25], showing associations between fibrin gel porosity and fibrinogen and lipoproteins, respectively, in patients with myocardial infarction at a young age. However, in one of those studies the strongest determinant of fibrin gel structure was found to be the acute-phase reactant orosomucoid [11], and an association was demonstrated between proneness to form a tight and rigid fibrin network and premature coronary artery disease [11].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the most powerful determinants of fibrin gel permeability (Ks) were changes in levels of P-fibrinogen and cholesterol. These findings are in line with studies by Fatah et al [11,25], showing associations between fibrin gel porosity and fibrinogen and lipoproteins, respectively, in patients with myocardial infarction at a young age. However, in one of those studies the strongest determinant of fibrin gel structure was found to be the acute-phase reactant orosomucoid [11], and an association was demonstrated between proneness to form a tight and rigid fibrin network and premature coronary artery disease [11].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with studies by Fatah et al [11,25], showing associations between fibrin gel porosity and fibrinogen and lipoproteins, respectively, in patients with myocardial infarction at a young age. However, in one of those studies the strongest determinant of fibrin gel structure was found to be the acute-phase reactant orosomucoid [11], and an association was demonstrated between proneness to form a tight and rigid fibrin network and premature coronary artery disease [11]. In a later study [25], also consisting of non-diabetic patients with coronary artery disease, the abnormalities of fibrin gel structure were related to an impaired fibrinolytic function secondary to a raised level of plasma plasminogen activator inhibitor 1 (PAI-1).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…19,20 After MI, fibrin clots have reduced permeability and a lower fiber mass-to-length ratio. 13,21 There are independent associations between permeability and the extent and severity of coronary artery stenosis and also of fibrinolytic activity. Patients with severe coronary artery disease have more rigid clot structures and an elevated fiber mass-to-length ratio.…”
Section: Abnormal Clot Architecture and Atherothrombotic Vascular Dismentioning
confidence: 99%